UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN TWO STAY TWO STRAY PADA SISWA KELAS VIID SMP MUHAMMADIYAH 1 WONOSARI - Novita Wardhaningsih; Benedictus Kusmanto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2015)
The purposes of this research was to describe the interest and achievement of mathematics in student D seventh grade junior high school Muhammadiyah 1 Wonosari using TSTS (Two Stay Two Stray). This research is Class Action Research (CAR). The technique of data done by questionnaire, tests and documentation. The results of research that the interest and achievement of mathematics is increased. The average percentage of student interest questionnaire at pre-cycle was 73,25%, became 73,32% at cycle I, and became 74,33% at cycle II. Average of achievement at pre-cycle 43,08 , 55,81 at the first cycle, and 63,13 at the second cycle. So, teachers can implement cooperative learning TSTS type as a variation of learning.